Pembuatan Aplikasi Kasir Sederhana Berbasis Website pada Toko Pelanggan Shop Bengkalis - Prahana, Aryando; Arif, Muhammad (Politeknik Kampar, 2025)
Pelanggan Shop is a fashion retail business located in Bengkalis that previously relied on a manual system for recording transactions, which often caused inefficiencies, data inaccuracies, and delays in reporting. To overcome these challenges, a web-based cashier application was developed using the Software Development Life Cycle (SDLC) method. This system is designed to support various business operations through key features such as login authentication, an interactive dashboard, product and category management, inventory control, cashier transaction processing, user management, and real-time reporting. The implementation of the system significantly improves the speed and accuracy of transactions, minimizes human errors, and facilitates efficient management of store data. Moreover, the application enables the store owner to access transaction and inventory data anytime and anywhere via the internet, promoting better decision-making and operational control. Overall, the adoption of this web-based cashier system enhances the effectiveness of business operations, increases productivity, and improves customer satisfaction by providing faster and more reliable service.